Satellite estimates of euphotic zone and Secchi disk depths in a colored dissolved organic matter-dominated inland water - Gomes, Ana Carolina [UNESP]; Alcantara, Enner [UNESP]; Rodrigues, Thanan; Bernardo, Nariane [UNESP] (Elsevier B.V., 2020)
The water transparency is an important parameter to water quality monitoring. To quantify the water transparency the attenuation coefficient, k(d), of the photosynthetically active radiation - PAR, k(d)(PAR), the euphotic zone depth (Z(eu)) and the Secchi disk depth (Z(SD)) are used. There is no investigation using satellite data about the water transparency for inland waters dominated by the chromophoric dissolved organic matter (CDOM), an optical significant substance (OSS) of dissolved organic matter and an important water quality indicator that affect the primary production, and its relation with Chl-a. Therefore, six models, among them empirical and semi-analytical, were evaluated for Z(eu) and one semi-analytical model was considered for Z(SD). The errors (unbiased absolute percentage error, epsilon - 30%) of empirical and semi-analytical models for Z(eu) estimations were similar; and an empirical model using k(d)(490) from Zhao et al. (2013) had the best performance (epsilon - 16%). The semi-analytical model from Lee et al. (2015) to estimate Z(SD) presented an error of 57%. The spatial distributions of Z(eu) and Z(SD) provided the observation of a seasonal pattern of water transparency parameters, with high values in dry season, when the OSS concentrations reduced.
Keywords: Water quality; Water transparency; Attenuation coefficient; Satellite data